Thermal performance analysis of a thermocline storage tank with integrated annular distributors - Junli, Chen; Yanping, Zhang; Chongzhe, Zou; Yulong, Xiao; Yuming, Ouyang (Frontiers in Energy Research, 2023)
The implementation of single-tank thermocline storage systems in concentrating solar power systems is a promising solution to improve their stability and continuity. However, flow uniformity within the tank is crucial for achieving optimal thermal efficiency. Distributors have been used to homogenize flow uniformity, and their geometrical parameters significantly impact the thermal performance. In this study, a transient three-dimensional model was developed to investigate the effect of annular distributor gaps on temperature and velocity distribution during the charging and discharging processes. The results showed that the use of annular distributors prevented maldistribution of the thermocline layer, resulting in improved flow uniformity. Furthermore, the discharging efficiency initially decreased and then increased as the gap increased from 30 mm to 80 mm. The minimum discharging efficiency of 72.8% was observed at a gap of 50 mm. Therefore, this study provides an effective method for optimizing the design of annular distributors and presents a creative approach for improving the flow uniformity in thermocline storage tanks.